Yield and Textural Characteristics of Panela Cheeses Produced with Dairy‐Vegetable Protein (Soybean or Peanut) Blends Supplemented with Transglutaminase. Issue 12 (9th November 2015) - Salinas‐Valdés, Alicia; De la Rosa Millán, Julián; Serna‐Saldívar, Sergio O.; Chuck‐Hernández, Cristina
Abstract: The study evaluated panela cheeses made from dairy‐plant protein blends, using soybean or peanut protein isolates, supplemented with transglutaminase (TG). Plant proteins were isolated using an alkaline extraction method followed by acid precipitation, and added to the dairy system in order to increase 50% or 100% the protein concentration. The total protein extraction for peanut and soybean isolates was 30.3% and 54.6%, respectively (based on initial protein content of sources), and no impairment of their essential amino acid profile was detected. Cheeses supplemented with TG and soybean showed the highest moisture and crude yield (>67.8% and 20.7%, respectively), whereas protein content was higher in the peanut isolate—added samples without TG (>67.4%). Cheese solids yield (ratio between final and initial solids) was higher for treatments with TG and 100% of plant protein addition (>50.7%). Regarding texture, 4 parameters were measured: hardness, cohesiveness, chewiness, and springiness. All cheeses containing soybean isolates and TG presented the highest chewiness and cohesiveness values, similar to those of the control treatment. Springiness was similar for all treatments, but hardness was higher in cheeses prepared with the peanut protein isolate added with TG. From these results it can be concluded that panela cheeses can be elaborated following a traditional procedure, but with the addition of soybean or peanut protein to the dairy ingredients. Cheeses containing these protein isolates showed higher protein than the milk control cheese and similar textural characteristics.